Evaluation of Bioactive Secondary Metabolites from Ponyfish Associated Bacteria (Photobacterium leiognathi) - Sangeswari Thirukumar; Uthra Selvaraj; Srichandan Rath; Kanchana Shankar; Arumugam Muthuvel (Journal of Tropical Biodiversity and Biotechnology, 2022)
The marine environment continues to surprise us by producing novel bioactive substances with a wide range of benefits for humans. Materials and Methods: Marine bioluminescent bacteria Photobacterium leiognathi was isolated from pony fish, Secutorruconius which was confirmed with microscopic and molecular characterization. The secondary metabolite of the isolated bacteria was extracted with dichloromethane. The chemical fingerprinting of the isolated metabolite was analyzed through TLC, FT-IR, and HPLC. The nature of the compound present in the metabolite was identified in the gas chromatography-mass spectrometry analysis (GC - MS). The isolated extract was investigated for its antibacterial property against 10 human pathogenic bacteria and also its antioxidant activity using different assays such as 1, 1-Diphenyl-2-picrylhydrazyl, Phosphomolybdenum, Metal chelating, Hydroxyl radical scavenging and hydrogen peroxide scavenging activity. Results: The Presence of functional groups including phenols, sugars, and amino acids in the extracts were identified by TLC. Totally, nine peaks were obtained for the crude extract through the FTIR spectrum range of 400 to 4000 cm-1 for the active sample. The DCM extract showed a broad spectrum of antibacterial activity against the six human bacterial pathogens. Secondary metabolites from the bioluminescent bacteria, P. leiognathi, have strong antioxidant properties. These results will be instrumental in developing novel products with biosensors and bio-imaging applications using P. leiognathi.